- TINDAK PIDANA PENCURIAN YANG DILAKUKAN SECARA BERSEKUTU STUDI PUTUSAN NOMOR 203/Pid.B/2021/PN.LLG: - - Junandri Caesar Putra; Dian Adriawan Daeng Tawang (Faculty of Law, Universitas Trisakti, 2023)
Theft is one of the most common criminal offenses, with a lot of news in various mass media, both electronic and print media. The crime of theft is usually motivated by the circumstances of the perpetrator's daily life. In this study, there is a case with the perpetrator named Rio Pratama bin Sarnubi committing a theft crime committed in concert, but the perpetrator's actions in verdict number 203/Pid.B/2021/PN.LLG were decided by article 365 paragraph (1) and paragraph (2) of the Criminal Code on violence. The main problems raised in this thesis are 2 (two), namely, How the Criminal Act by the Perpetrator is in accordance with Article 363 paragraph (1) 4 of the Criminal Code and How the Act Against the Crime of Theft Committed in Accord Decision No. 203/Pid.B/2021/PN.LLG. The actions of the perpetrator are included in the crime of theft, in this case the actions are regulated in Article 363 paragraph (1) 4th of the Criminal Code regarding theft committed jointly. The Linggau District Court in deciding a criminal offense is not in accordance with the applicable laws and regulations. Judges in handling a criminal offense should understand that the principle of legality and the principle of legal certainty must be prioritized in seeing the actions and facts in order to decide a case appropriately.